TEACHER'S PEDAGOGY COMPETENCE AND CHALLENGES IN IMPLEMENTING INCLUSIVE LEARNING IN SLOW LEARNER - Mumpuniarti Mumpuniarti; Rendy Roos Handoyo; Diajeng Tyas Phytanza; Dewi Barotuttaqiyah (LPMPP Universitas Negeri Yogyakarta, 2020)
Regular teacher training for schools implementing inclusive education is expected to affect the teachers mastery of learning competency. The results of the training need to be examined to determine some aspects of competency that need to be trained further, so that it is beneficial to an ideal inclusive education. This study aims to describe regular teachers most important aspects of competency, as well as their obstacles and challenges in implementing learning in inclusive schools. The research instrument consisted of 21 closed-ended questions and 4 open-ended questions. The data from the 21 closed questions were analyzed using percentage of answers from respondents, and respondents' answers to the open-ended questions were analyzed using the categorization of the challenges faced by teachers for inclusive learning. The findings from the study shows that the inclusive teachers possessed the pedagogical competence to help them face the diversity of the students from various aspects; the regular teachers were able to manage the diverse learning needs; the regular teacher competence to help slow-learners was able to change abstract concepts into concrete forms; the regular teachers found some obstacles in managing students diversity; and the regular teachers challenges in implementing inclusive education included diverse teaching methods, competence to modify learning, and professional improvement achievement.